A midgut‐specific lytic polysaccharide monooxygenase of Locusta migratoria is indispensable for the deconstruction of the peritrophic matrix. (28th February 2022) - Qu, Ming‐Bo; Guo, Xiao‐Xi; Kong, Lin; Hou, Ling‐Jie; Yang, Qing
Abstract: Lytic polysaccharide monooxygenases (LPMOs) are important enzymes that boost the hydrolysis of recalcitrant polysaccharides, such as chitin. They are found extensively in different insect species and are classified as auxiliary activities family 15 (AA15) LPMOs (LPMO15). Some of them were identified from the insect midgut and proven to act on chitin. However, knowledge about their physiological roles during insect growth and development remains limited. Here, we found that midgut‐specific LPMO15 s are widely distributed in different insect orders, such as the orthopteran Locusta migratoria and the lepidopteran Bombyx mori . Using L. migratoria as a model insect, the function of midgut‐specific LmLPMO15‐3 during development was investigated. Double‐stranded RNA‐mediated downregulation of LmLPMO15‐3 expression at the 4th or 5th instar nymph stage severely decreased the survival rate and resulted in lethal phenotypes. Hematoxylin and eosin staining results indicated that the deficient individuals exhibited incompletely digested peritrophic matrix (PM), which suggested that LmLPMO15‐3 is essential for the deconstruction of the PM during molting. This study provides direct evidence of the physiological importance of a midgut‐specific LPMO15 during insect development. As L. migratoria is one of the most destructive agricultural pests, LmLPMO15‐3 is a potential target for pest management.